Edukasi dan Penapisan Obesitas pada Remaja di Panti Asuhan Agape, Jakarta Utara - Alexander Halim Santos; Giovanno Sebastian Yogie; Ryan Dafano Putra Mahendri; Daiva Pattra Yoe; Indah Elvina V. Pangaribuan; Alicia Herdiman (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
340 million children and adolescents aged 5-19 years worldwide are overweight and obese. Education and screening are efforts made to prevent obesity. This activity was carried out on 37 teenagers at Pondok Kasih Agape Orphanage, North Jakarta, in the form of counseling, physical examinations/screening, and health consultation. Obesity education and screening in adolescents is an important thing to do to prevent obesity in adolescents and its complications. It is hoped that the education provided can change aspects of lifestyle so that various changeable risk factors can be avoided and the incidence of obesity in adolescents can be avoided. Furthermore, these lifestyle changes can have an impact on society, so that the incidence of obesity in the community can be reduced.